A random clinical experimental study on the effect of mechanical vibration on the gaseous exchange and lung functions of patients with acute lung injuries - Wessels, S. P.(Susara Philippina) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.(Physiotherapy)) -- University of Stellenbosch, 1991.